2013
DOI: 10.2528/pier12080109
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Only Synthesis of Flat Aperiodic Reflectarrays

Abstract: Abstract-A phase-only power pattern synthesis technique for flat (aperiodic) microstrip reflectarrays with elements arranged on a nonregular lattice is presented. The approach mitigates the typical design issues of reflectarray antennas related to the computational burden and to the possible occurrence of suboptimal solutions which are here even more significant due to the non-regular element lattice. This is done by a convenient two-stage procedure for choosing the starting point of the iterations and by prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…The validity of the PO model for the common case of a rectangular patch has been discussed in [27]. Furthermore, the PO approach is able to take into account, although of course in an approximate way, the mutual coupling effects between each element and the surrounding reflectarray elements as well as the specular reflection from the ground plane supporting the patches.…”
Section: The Po Radiating Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The validity of the PO model for the common case of a rectangular patch has been discussed in [27]. Furthermore, the PO approach is able to take into account, although of course in an approximate way, the mutual coupling effects between each element and the surrounding reflectarray elements as well as the specular reflection from the ground plane supporting the patches.…”
Section: The Po Radiating Modelmentioning
confidence: 99%
“…Finally, numerical simulations have indicated that the radiation of reflectarrays synthesized under the PO model have already a good degree of matching with the radiation of the same reflectarray as evaluated by more "accurate" models [37].…”
Section: The Po Radiating Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This work focuses on the synthesis of reconfigurable multiple patterns with fewer elements by selecting the common ones with optimized excitation amplitudes and phases. Some synthesis methods by using nonuniform element positions [16][17][18][19][20][21][22], or by applying thinning techniques [23][24][25], have been presented to effectively reduce the number of elements. However, these reviewed techniques are proposed for the synthesis of single-pattern arrays.…”
Section: Introductionmentioning
confidence: 99%